Valid evaluation of volatile flavor composition of fresh and dehydrated Tuber indicum with different drying methods - Ning Ma; Fei Pei; Jie Yu; Siyu Wang; Chi-Tang Ho; Kaimei Su; Qiuhui Hu (CyTA - Journal of Food, 2018)
The effects of three drying methods on volatile flavor components of Tuber indicum were studied. After hot air drying (AD), vacuum drying (VD), and vacuum-freeze drying (FD), flavor components were analyzed by headspace solid phase microextraction GC-MS and electronic nose (E-nose). The results from GC-MS showed that aldehydes (54.8%) and alcohols (31.4%) are the two dominant chemical species in fresh T. indicum and eight carbon (C8) compounds including 1-octen-3-ol, 3-octanol, n-octanol, 3-octanone. After dehydrating, C8 compounds, aldehyde, and ester components reduced, while alkanes, heterocyclic, and sulfur components were produced. Multivariate statistical analysis of the GC-MS revealed the components responsible for the chemical differences between fresh and three drying samples. In addition, E-nose could discriminate fresh and three drying samples. The result obtained by E-nose showed good identity compared with GC–MS. Therefore, FD was the optimal dehydrating method to preserve Tuberaceae with the most retained fresh flavor.